Turnaround strategies : key factors for corporate recovery in the electricity industry of New Zealand and the Philippines - Joson, Gerardo R. (Curtin University, 1997)
This research is about the problem of identifying key factors for corporate recovery of electric utilities in New Zealand and the Philippines. Its primary objective is to learn from the experiences of three regulated government utilities and one small private distributor that are involved in the three sectors of electricity business in power generation, transmission and distribution. How these firms survived their decline problems, and managed and sustained their turnaround efforts is the focus of this study. The results indicate the importance of change management, leadership, cost reduction and financial control in reversing the decline of these firms. Also underscored are the crucial role of efficiency improvement and achievement of profit together with winning employee commitment and broad stakeholder support in sustaining the recovery effort.These comparative case studies were undertaken at a time when crises and turbulence affected the management and organisation of electricity businesses in the Asia/Pacific region, particularly New Zealand and the Philippines. Electric utilities in both countries are regulated and less vertically integrated than anywhere else in the region. Significant changes to the ownership and control of these firms and their competitive relationships over the past decade have complicated the way strategic problems and issues have to be resolved. In the meantime, threats and pressures from all stakeholders have made the management and operations of these utilities difficult.Thus, a critical review of their specific circumstances and predicaments is in order for similarly affected enterprises to avoid past errors and to replicate only the strategies that may suit them. In this regard, this work contributes to the enrichment of the existing body of knowledge in business policy and strategic management that has been fast evolving during the nineties in electric utilities around the world.